In Situ One‐Pot Synthesis of MOF–Polydopamine Hybrid Nanogels with Enhanced Photothermal Effect for Targeted Cancer Therapy. Issue 6 (14th April 2018) - Wang, Dongdong; Wu, Huihui; Zhou, Jiajia; Xu, Pengping; Wang, Changlai; Shi, Ruohong; Wang, Haibao; Wang, Hui; Guo, Zhen; Chen, Qianwang
Abstract: Herein, a simple one‐pot way is designed to prepare a type of multifunctional metal–organic framework (MOF)‐based hybrid nanogels by in situ hybridization of dopamine monomer in the skeleton of MnCo. The resultant hybrid nanoparticles (named as MCP) show enhanced photothermal conversion efficiency in comparison with pure polydopamine or MnCo nanoparticles (NPs) synthesized under a similar method and, therefore, show great potential for photothermal therapy (PTT) in vivo. The MCP NPs are expected to possess T 1 positive magnetic resonance imaging ability due to the high‐spin Mn‐N6 ( S = 5/2) in the skeleton of MnCo. To improve the therapy efficiency as a PTT agent, the MCP NPs are further modified with functional polyethylene glycol (PEG) and thiol terminal cyclic arginine–glycine–aspartic acid peptide, respectively: the first one is to increase the stability, biocompatibility, and blood circulation time of MCP NPs in vivo; the second one is to increase the tumor accumulation of MCP‐PEG NPs and improve their therapeutic efficiency as photothermal agent. Abstract : A one‐pot method to prepare multifunctional hybrid nanogels by in situ hybridization of dopamine monomer in the skeleton of MnCo is reported. After surface modification with polyethylene glycol and targeting molecules, the resultant hybrid nanoparticles with enhanced photothermal conversion efficiency demonstrate improved blood circulation time and tumor accumulation and, therefore, show great potential to kill tumor in vivo under near infrared (NIR) irradiation.